Discourse Analysis in the ESL Classroom - Nemat Tabrizi, Amir Reza; Gupta, Deepti; Saxena, Mohita (Widya Mandala Catholic University Surabaya, 2014)
This article attempts a user-friendly definition of discourse analysis. By defining it in this manner, the authors hope to encourage teachers to use it in their ESL classrooms. To this end, they suggest certain concrete measures that bring discourse analysis into the ESL classroom.